2016
DOI: 10.1016/j.cub.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Increased Global Functional Connectivity Correlates with LSD-Induced Ego Dissolution

Abstract: Lysergic acid diethylamide (LSD) is a non-selective serotonin-receptor agonist that was first synthesized in 1938 and identified as (potently) psychoactive in 1943. Psychedelics have been used by indigenous cultures for millennia [1]; however, because of LSD's unique potency and the timing of its discovery (coinciding with a period of major discovery in psychopharmacology), it is generally regarded as the quintessential contemporary psychedelic [2]. LSD has profound modulatory effects on consciousness and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
409
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(475 citation statements)
references
References 42 publications
37
409
4
Order By: Relevance
“…Carhart-Harris et al [23] found that the functional disconnectivity was strongly correlated with the rating of ego “dissolution” that was inferred to reflect the importance of this circuit to maintain the sense of self. Tagliazucchi et al [24], employing a slightly different approach, noted that the LSD effects enhanced global between-module interactions within those regions rich in 5-HT 2a receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Carhart-Harris et al [23] found that the functional disconnectivity was strongly correlated with the rating of ego “dissolution” that was inferred to reflect the importance of this circuit to maintain the sense of self. Tagliazucchi et al [24], employing a slightly different approach, noted that the LSD effects enhanced global between-module interactions within those regions rich in 5-HT 2a receptors.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, intuitively, the psychedelic state wouldn't appear to be functionally optimal. The hyper-connectivity which characterizes it (Tagliazucchi et al, 2016) is in general associated brain pathology (Whitfield-Gabrieli et al, 2009; Supekar et al, 2013; Hillary et al, 2015). During the psychedelic state the number of forbidden connectivity patterns may decrease, but some of these patterns may be associated with suboptimal (possibly even functionally detrimental) states.…”
Section: Psychedelic State and Criticalitymentioning
confidence: 99%
“…Clinical experimental research with LSD has recently seen a resurgence (Carhart-Harris et al 2016b; Carhart-Harris et al 2015; Carhart-Harris et al 2016c; Dolder et al 2015b; Dolder et al 2016; Kaelen et al 2015; Kaelen et al 2016; Lebedev et al 2016; Roseman et al 2016; Schmid et al 2015; Speth et al 2016; Strajhar et al 2016; Tagliazucchi et al 2016; Terhune et al 2016). An increasing amount of data has been generated on the effects of LSD (75 μg) on various neuronal correlates of brain activation (Carhart-Harris et al 2016c; Kaelen et al 2016; Lebedev et al 2016; Roseman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The 5D-ASC scale has been used in all of the recent experimental studies with LSD (Carhart-Harris et al 2016b; Carhart-Harris et al 2016c; Schmid et al 2015; Tagliazucchi et al 2016) and with many other psychedelics, providing an opportunity to compare findings between studies and across substances and research groups. Thus, the present study assessed LSD dose- and plasma concentration-response functions using the 5D-ASC scale in 40 subjects (Dolder et al 2015b; Dolder et al 2016; Schmid et al 2015), thus allowing comparisons with other studies that used the 5D-ASC scale but did not determine plasma LSD concentrations (Carhart-Harris et al 2016b; Carhart-Harris et al 2016c; Kaelen et al 2016; Lebedev et al 2016; Roseman et al 2016; Speth et al 2016; Tagliazucchi et al 2016; Terhune et al 2016). A third goal of the present study was to assess associations across subjects between the peak and total plasma exposure to LSD and its effects on 5D-ASC scale scores (Studerus et al 2010).…”
Section: Introductionmentioning
confidence: 99%